UV-Spectral Behaviour of Some Newly Synthesised Half-Esters - Mohan Adak, Mohini (Asian Journal of Chemistry, 2010)
As an application of the newly deviced an efficient method of selective esterification several new half-esters were prepared. For their identification and characterisation spectral data become very helpful. The UV-spectral data of several half-esters, prepared by selective esterification of the aliphatic primary carboxylic groups of carboxy phenoxyacetic acids (o, m and p) and carboxy phenylacetic acids (o, m and p) were collected. The isomeric half-esters, prepared by partial hydrolysis of the corresponding dialkyl esters, were also examined.